2011
DOI: 10.1007/7854_2011_198
|View full text |Cite
|
Sign up to set email alerts
|

What is in that Drink: The Biological Actions of Ethanol, Acetaldehyde, and Salsolinol

Abstract: Alcohol abuse and alcoholism represent substantial problems that affect a large portion of individuals throughout the world. Extensive research continues to be conducted in an effort to identify the biological basis of the reinforcing properties of alcohol in order to develop effective pharmacotherapeutic and behavioral interventions. One theory that has developed within the alcohol field over the past 4 decades postulates that the reinforcing properties of alcohol are due to the action of the metabolites/prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 129 publications
(144 reference statements)
1
27
0
1
Order By: Relevance
“…Alcohol abuse and alcoholism represent substantial problems that affect a large portion of the general public 1 . Alcohol is known to cause structural and functional abnormalities to the brain 1-6 including the significant risk associated with chronic alcohol abuse, particularly disorders of the central nervous system (CNS) 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol abuse and alcoholism represent substantial problems that affect a large portion of the general public 1 . Alcohol is known to cause structural and functional abnormalities to the brain 1-6 including the significant risk associated with chronic alcohol abuse, particularly disorders of the central nervous system (CNS) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol is known to cause structural and functional abnormalities to the brain 1-6 including the significant risk associated with chronic alcohol abuse, particularly disorders of the central nervous system (CNS) 7 . Alcohol is known to attenuate phagocytosis 3, 8, 9 , proliferation 4 , expression of neurotrophic factor brain-derived neurotrophic factor (BDNF) in hippocampus 10 and apoptosis in microglia 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Review of the old and newer data clearly reveals that within the well-established brain reward circuitry, alcohol metabolites (e.g., dopamine and acetaldehyde) are involved in alcohol induced effects as indicted herein: (1) biologically active metabolites of alcohol can directly or indirectly increase the activity of VTA dopamine neurons, (2) alcohol and alcohol metabolites are reinforcing within the mesolimbic dopamine system, (3) inhibiting the alcohol metabolic pathway inhibits the biological consequences of alcohol exposure, (4) alcohol consumption can be reduced by inhibiting/attenuating the alcohol metabolic pathway in the mesolimbic dopamine system, (5) alcohol metabolites can alter neurochemical levels within the mesolimbic dopamine system, and (6) alcohol interacts with alcohol metabolites to enhance the actions of both compounds (Deehan, Hauser, Wilden, Truitt, & Rodd, 2013). Accordingly, there is a positive relationship between alcohol and alcohol metabolites in regulating the alcohol intake, and these biological consequences lead to an escalation to alcoholism (Deehan, Brodie, & Rodd, 2013).…”
Section: Relationship To Alcohol Use and Abusementioning
confidence: 99%
“…Accordingly, there is a positive relationship between alcohol and alcohol metabolites in regulating the alcohol intake, and these biological consequences lead to an escalation to alcoholism (Deehan, Brodie, & Rodd, 2013). Furthermore, fortification of these results has adequately shown that salsolinol can induce dopamine release in the mesolimbic brain region, supporting earlier indications (Hipolito, Sanchez-Catalan, Granero, & Polache, 2009; Melchior, Simpson, & Myers, 1978).…”
Section: Relationship To Alcohol Use and Abusementioning
confidence: 99%
See 1 more Smart Citation